Testing the Validity of Gender Ideology Items by Implementing Probing Questions in Web Surveys. Issue 2 (May 2013) - Behr, Dorothée; Braun, Michael; Kaczmirek, Lars; Bandilla, Wolfgang
This article examines the use of probing techniques in web surveys to identify validity problems of items. Conventional cognitive interviewing is usually based on small sample sizes and thus precludes quantifying the findings in a meaningful way or testing small or special subpopulations characterized by their response behavior. This article investigates probing in web surveys as a supplementary way to look at item validity. Data come from a web survey in which respondents were asked to give reasons for selecting a response category for a closed question. The web study was conducted in Germany, with respondents drawn from online panels ( n = 1, 023). The usefulness of the proposed approach is shown by revealing validity problems with a gender ideology item.